Difficulties in Accessing Medication Records at the Time of a Large-Scale Disaster. (5th April 2023) - Ueno, Fumihiko; Murakami, Keiko; Nagai, Masato; Matsubara, Hiroko; Oonuma, Tomomi; Matsuzaki, Fumiko; Noda, Aoi; Ishikuro, Mami; Obara, Taku; Kuriyama, Shinichi
Abstract: Objective: In a large-scale disaster, medical professionals need to access medication records and provide medicines to people who cannot return home to take their daily medicines. We investigated the proportion of carrying the paper notebook or availability of the smartphone application of the medication record among people who are assumed to have difficulty in taking their medicines during large-scale disasters. Methods: In Japan, a web-based survey was conducted in 2018 by randomly selecting adults ≥ 20 years of age. Results: There were 2286 medication record owners in 3082 participants. Of the medication record owners, 784 (34.3%) took medicines that could not be missed for even a day. Among them, 724 used paper notebooks alone, 26 used smartphone applications alone, and 34 used both. Among the 724, 208 (28.8%) always carried a paper notebook. Among the 26, 16 (61.5%) could use their applications anytime. Therefore, among the 784, at least 560 (71.4%) could not always access their medication information. Conclusions: An awareness campaign to carry paper notebooks and install applications for medication records should be held, since only a limited number of people carry their medication records and always have access to their medication information.